A New Vision for Islamic Pasts and Futures - Bashir, Shahzad (The MIT Press, 2022)
This groundbreaking, born-digital work invites readers to imagine Islam anew. Moving beyond conventional theological, nativist, and orientalist approaches, Shahzad Bashir decenters Islam from a geographical identification with the Middle East, an articulation through men's authority alone, and the assumption that premodern expressions are more authentically Islamic than modern ones. Focusing on time as a human construct, A New Vision for Islamic Pasts and Futures interprets stories and images, paying attention to evidence and methods of interpretation. Islam, in Bashir's telling, is a vast net of interconnected traces that appear to be different depending on the vantage from which they are seen. Complementing narrative with extensive visual evidence, the multimodal digital form enacts the multiplicity of the project's analyses and perspectives, conferring a shape-shifting quality that bridges the gap between sensing Islam and understanding it, between feeling it as a powerful presence and analyzing it through intellectual means. This interactive, open-access edition allows readers to enter Islam through a diverse set of doorways, each leading to different time periods across different parts of the world. Bashir discusses Islam as phenomenon and as discourse-observed in the built environment, material objects, paintings, linguistic traces, narratives, and social situations. He draws on literary genres, including epics, devotional poetry and prayers, and modern novels; art and architecture in varied forms; material culture, from luxury objects to cheap trinkets; and such forms of media as photographs, graffiti, and films. The book's layered digital interface allows for an exploration of and engagement with this rich visual material and multimedia evidence not possible in a printed volume. A collaboration between the MIT Press and the Digital Publications Initiative of Brown University. Supported by the Andrew W. Mellon Foundation, the Carnegie Corporation of New York, the MIT Press, and the Digital Publications Initiative of Brown University. The URL for this project will be islamic-pasts-futures.org